Resurrection of Crypturgus subcribrosus Eggers 1933 stat. n., and its close phylogenetic relationship to Nearctic Crypturgus (Coleoptera, Scolytinae) - Jordal, Bjarte H.; Kníšek, Miloš (Zootaxa, 2007)
Crypturgus subcribrosus Eggers is removed from synonymy under C. cinereus (Herbst) and reinstated as a valid species based on evidence from DNA sequence data and morphological features. Phylogenetic analyses of Elongation Factor 1α and Cytochrome Oxidase I sequences in conjunction with morphological characters revealed a sister relationship between C. subcribrosus and two Nearctic species of Crypturgus, with C. cinereus unrelated to any of these taxa. Type material of C. cinereus has been located and lectotype with paralectotypes are designated. Amended diagnoses that include DNA barcodes are presented for C. subcribrosus and C. cinereus together with an identification key to the Fennoscandian species of Crypturgus.